Nano-based perivascular intervention sustains a nine-month long-term suppression of intimal hyperplasia in vein grafts - Takuro Shirasu; Go Urabe; Nisakorn Yodsanit; Yitao Huang; Ruosen Xie; Matthew S. Stratton; Matthew Joseph; Zhanpeng Zhang; Yuyuan Wang; Jing Li; Runze Tang; Lynn M. Marcho; et al. (Bioactive Materials)
Open vascular reconstructions (OVR), including bypass grafts and dialysis access, are standard treatments for cardiovascular and renal diseases. Unfortunately, OVR often fail largely due to intimal hyperplasia (IH), and there are no clinical methods to prevent this complication. Perivascular drug administration during OVR presents a promising strategy for IH suppression. However, durations of drug release from carriers are generally short whereas sustained efficacy is essential for clinical success. This raises a critical question in clinical translation: can IH suppression be realistically maintained long-term (e.g., over 6 months) with short-term perivascular interventions? To address this question, we modified a rat vein-graft model to prolong IH progression. We then applied Pericelle, a nanoparticle/hydrogel hybrid system that we developed for perivascular delivery of rapamycin, an established IH-inhibitory drug. Surprisingly, despite short (∼3-month) drug release, Pericelle demonstrated IH suppression throughout 3, 6, and 9 months with IH reduced from 115.58 ± 27.89 to 40.34 ± 5.18 at 9 months (P < 0.05, n = 6 rats), as indicated by morphometric analysis. Live animal ultrasonography showed the same trend. Consistently, histone-3 lysine-27 trimethylation, an epigenetic mark associated with IH progression, was decreased at 6 months after Pericelle treatment. Moreover, Pericelle exhibited promising efficacy in mitigating IH in a porcine model of arteriovenous fistula that mimics dialysis access. These results suggest that Pericelle-mediated suppression of IH in rat vein-grafts extends much beyond drug release, offering potential solutions to longstanding translational challenges in reducing OVR failure.